Evaluating health promotion practice and methods - Thorogood, Margaret; Coombes, Yolande (Oxford : Oxford University Press, 2010)
The third edition of this highly successful book has been fully revised and updated to reflect the ongoing developments in the field of health promotion, to help those in health promotion choose and implement accurate, reliable, and evidence-based evaluation methods.
Previous ed.: 2004.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Health promotion -- Evaluation; Evaluation research (Social action programs)